Mental Health of High School Students: A Proposed Program - Qua, Mariel; Vergara, Hazel (International Journal of Sustainability and Advanced Integrated Research, 2026)
Adolescence is a critical developmental period in which academic demands, peer relationships, family concerns, and post-pandemic adjustment may significantly influence mental health. This study assessed the mental health status of high school students at Laguna Eastern Academy of Santa Rosa, Inc. (LEASRI) and used the findings as basis for a proposed school-based mental health program. Anchored on Social-Emotional Learning (SEL), the study employed a mixed-methods design during the 2025–2026 school year. Quantitative data were collected from 406 junior and senior high school students using the Mental Health Inventory-38 (MHI-38), while qualitative data were obtained through focus group discussions with 45 students identified as needing closer attention based on their anxiety, depression, and behavioral/emotional control scores. Descriptive statistics were used for the survey data, and thematic analysis was applied to the qualitative responses. Results showed that students generally experienced mild anxiety and mild depression, minimal loss of behavioral and emotional control, and mild psychological distress. Despite these concerns, students demonstrated moderate positive affect, moderate emotional ties, moderate life satisfaction, and an overall high level of psychological well-being. The overall Mental Health Index indicated high mental health or high well-being. Qualitative findings revealed that academic pressure, simultaneous school requirements, family-related concerns, overthinking, burnout, and fear of judgment were the most common sources of distress. Students also emphasized the need for visible, accessible, confidential, and non-judgmental support systems, including counseling services, safe spaces, mental health awareness activities, and reduced academic overload. Based on the findings, a school-based mental health program is proposed to strengthen mental health literacy, social-emotional competencies, support systems, and early intervention mechanisms in the school setting. The study underscores the need for schools to treat mental health as an essential component of student development and academic success.
Keywords: mental health; high school students’ mental health; MHI-38; mental health program